Strategy for Cultivation of Islamic Values in Madrasah and Community - Jannah, Raudhatul; Meisya, Rovika (Sunan Kalijaga International Journal on Islamic Educational Research, 2023)
Cultivating Islamic values has great urgency for the continuity of life in society. To form a safe and comfortable society. So it is necessary to know the right strategies for cultivating Islamic values in a society where one of the main forums is the madrasah. This study uses a qualitative method of literature. Miles and Huberman's data analysis techniques, namely data reduction, data display, and drawing conclusions. Based on the documents that have been collected and analyzed, Islamic values are divided into three aspects, namely aqidah, worship, and morals. Instilling these values in madrasas and society can be pursued with various strategies, namely: Modeling Strategy, Habituation Strategy, Ibrah, and Amtsal Strategy, Advice Strategy, Promise and Threat Strategy (Targhib wa tarhib), Discipline Strategy, Power Strategy, Persuasion Strategy, Education Regulation Strategy. These strategies can be adapted to the circumstances or characteristics of the madrasa and society so that they are considered capable of cultivating Islamic values themselves.